2018
DOI: 10.1074/jbc.m117.778399
|View full text |Cite
|
Sign up to set email alerts
|

Transcriptionally inducible Pleckstrin homology-like domain, family A, member 1, attenuates ErbB receptor activity by inhibiting receptor oligomerization

Abstract: Feedback control is a key mechanism in signal transduction, intimately involved in regulating the outcome of the cellular response. Here, we report a novel mechanism by which PHLDA1, Pleckstrin homology-like domain, family A, member 1, negatively regulates ErbB receptor signaling by inhibition of receptor oligomerization. We have found that the ErbB3 ligand, heregulin, induces expression in MCF-7 cells. Transcriptionally-induced PHLDA1 protein directly binds to ErbB3, whereas knockdown of increases complex for… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
9
0
2

Year Published

2019
2019
2023
2023

Publication Types

Select...
5
1
1
1

Relationship

3
5

Authors

Journals

citations
Cited by 11 publications
(13 citation statements)
references
References 51 publications
(42 reference statements)
2
9
0
2
Order By: Relevance
“…It has been implicated in the regulation of cell death and suppression of metastasis in cancers [33–35], and its expression is significantly reduced in human cancers [36, 37]. PHLDA1 overexpression significantly inhibits the phosphorylation and activation of Akt (also known as protein kinase B) [36, 38]. Akt1 may act to enhance HIV replication through promoting the survival of infected cells [39].…”
Section: Discussionmentioning
confidence: 99%
“…It has been implicated in the regulation of cell death and suppression of metastasis in cancers [33–35], and its expression is significantly reduced in human cancers [36, 37]. PHLDA1 overexpression significantly inhibits the phosphorylation and activation of Akt (also known as protein kinase B) [36, 38]. Akt1 may act to enhance HIV replication through promoting the survival of infected cells [39].…”
Section: Discussionmentioning
confidence: 99%
“…Gene silencing in MCF-7 cells performed by reverse transfection of 30 nM of SMARTpool ON-TARGETplus siRNA (Horizon Discovery, UK), targeting PML (L-006547-00) and Non-targeting Pool (D-001810-10) in 96well-plates, as described previously 51 .…”
Section: Gene Silencing With Sirnamentioning
confidence: 99%
“…However, during this process, we found that the integration of independently developed mathematical models is not simple. Because an integrated model becomes extremely large, the network contains multiple non-linear regulatory mechanisms such as feedback loops [ 21 , 22 , 23 , 24 , 25 ], and the available experimental data is limited. Therefore, it was difficult to obtain reproducible parameters (e.g., rate constants of enzymes and protein interactions) by minimizing an objective function, i.e., the distance between simulated values and experimental data [ 26 ].…”
Section: Introductionmentioning
confidence: 99%